2003
DOI: 10.1080/15287390390211342
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorines Affect the Major Androgenic Hormone, Testosterone, in Male Polar Bears ( Ursus Maritimus ) at Svalbard

Abstract: Normal sexual development and subsequent reproductive function are dependent on appropriate testosterone production and action. The regulation of steroid hormones, including androgens, can be influenced by both biological and environmental factors, including environmental chemicals. Concentrations of organochlorines are considerably greater in Svalbard polar bears than in polar bears from other regions. Between 1995 and 1998, samples were collected from 121 male polar bears (Ursus maritimus) from the Svalbard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 56 publications
4
65
1
4
Order By: Relevance
“…Rylander et al (2006) found no associations between serum PCB153 and testosterone concentrations in middle-aged and elderly men. In male polar bears, serum PCB levels are associated with lower serum testosterone levels (Oskam et al, 2003). The differences between our observations and most published data might, however, at least in part, stem (see also below) from the fact that our observations relate to relatively low concentrations, which are much lower than those that occurred during the Yucheng incident and than the concentrations used in animal experiments.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Rylander et al (2006) found no associations between serum PCB153 and testosterone concentrations in middle-aged and elderly men. In male polar bears, serum PCB levels are associated with lower serum testosterone levels (Oskam et al, 2003). The differences between our observations and most published data might, however, at least in part, stem (see also below) from the fact that our observations relate to relatively low concentrations, which are much lower than those that occurred during the Yucheng incident and than the concentrations used in animal experiments.…”
Section: Discussioncontrasting
confidence: 56%
“…The differences between our observations and most published data might, however, at least in part, stem (see also below) from the fact that our observations relate to relatively low concentrations, which are much lower than those that occurred during the Yucheng incident and than the concentrations used in animal experiments. The PCB concentrations in the polar bears (Oskam et al, 2003) were more than hundred times higher than in the Flemish adolescents in our study. The biological plausibility of our observations might rest on the anti-estrogenic activity of PCBs (Kruger et al, 2008), as endogenous estrogens inhibit testosterone production through actions on the testis or indirectly on the hypothalamic-pituitary axis (Sanford, 1985;Delbes et al, 2005).…”
Section: Discussionmentioning
confidence: 67%
“…In the male population of Florida panthers (Felix concolor coryi) sperm abnormalities, including low ejaculate volume and sperm concentration, poor sperm motility and a high proportion of abnormal sperm, as well as an increase in cryptorchidism, have been reported (Facemire et al 1995). A decrease in plasma testosterone levels has been reported for juvenile alligators (Alligator mississipienisis) in Lake Apopka, Florida, as well as in polar bears (Ursus maritimus) from the Svalbard area in the Norwegian Arctic , Oskam et al 2003. It is not easy to compare and integrate results from wildlife studies since data that report possible relationships between PCB exposure and adverse reproductive effects are often based upon a diversity of species, different exposure conditions, and differences in exposure levels and timing and duration of the exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies dealing with the effects of CHCs on polar bear health have raised significant concerns. As recently summarized by Fisk et al (2005-this issue), the current understanding of contaminant-induced biological effects in polar bears points to evidence that chronic exposure to CHCs and their metabolites may compromise endocrine functions and homeostasis (Sandau, 2000;Norstrom, 2000;Skaare et al, 2001a;Letcher et al, 2002;Haave et al, 2003;Oskam et al, 2003Oskam et al, , 2004Braathen et al, 2004), immune functions (Bernhoft et al, 2000;Norstrom, 2000Norstrom, , 2001Skaare et al, 2001b;Larsen et al, 2002;Lie et al, 2004aLie et al, , 2005Kirkegaard et al, 2005), cub and reproductive female survival , reproduction and development (Wiig et al, 1998), and hepatic P450-enzymes induction (Bandiera et al, 1995;Letcher et al, 1996).…”
Section: Introductionmentioning
confidence: 99%